PROFILE OF ORAL TUMORS AT ULIN HOSPITAL, BANJARMASIN: A RETROSSPECTIVE CROSS-SECTIONAL STUDY - Carabelly, Amy Nindia; Sembiring Meliala, Gabriel Afreulinta; Azizah, Aulia; Hamdani, Riky; Taufiqurrahman, Irham (Dentino: Jurnal Kedokteran Gigi, 2026)
Background: Oral tumors are excessive cell growths in the oral cavity and rank 16th worldwide in incidence. However, Indonesian Health Surveys and Profiles do not yet include data on oral tumors. Ulin Hospital is the referral hospital for oral tumor cases in South Kalimantan. Purpose: A retrospective cross-sectional study to analyze the profile of oral tumor cases at Ulin Hospital, Banjarmasin, in 2019-2021.Methods:A retrospective cross-sectional study of the medical records of patients diagnosed with oral tumors at Ulin Hospital between 2019 and 2021. Inclusion criteria were all patient medical records with complete variables. The variables were age, gender, tumor type, tumor location, and therapy. Chi-square analysis was used.  Results: Oral cavity tumors are predominantly malignant, with squamous cell carcinoma (SCC) being the most common. SCC most commonly occurs in people aged 36–65 years, with the tongue being the most common location. There was no significant association between the year of incidence and tumor type (p>0.05), but there was a significant association between gender and tumor type (p<0.05). The most frequently administered therapy was chemotherapy. The most common benign oral tumors were pleomorphic adenoma (in 2019 and 2021) and fibromatous epulis (in 2020). Conclusions: Oral cavity tumors at Ulin Hospital are predominantly SCC, with gender being a significant factor in tumor type. Therefore, early detection and accurate diagnosis are crucial to improving patient prognosis.Keywords:Benign Tumor, Chemotherapy, Malignant Tumor, Oral Tumor, Squamous Cell Carcinoma